2021
DOI: 10.1111/ijun.12282
|View full text |Cite
|
Sign up to set email alerts
|

The use of mobile applications in urology. A systematic review

Abstract: Can the use of mobile applications (apps) improve quality of life and disease management in adult patients with urologic disease? Technology has created new opportunities to promote behavioural change in the daily lives of patients. One third of adults in the United States who own smartphones or tablets use health apps to improve their health. The aim of this review was to analyse whether use of mobile apps improves the quality of life and symptom management of urological patients. Databases: PubMed, CINAHL, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Scientifically correct and personalized information enables patients to understand, evaluate and choose from a variety of safe and effective treatments in a conscious and truly autonomous manner. 52,55 This approach would also lay the necessary foundations for avoiding self-medication and autonomous therapeutic interruptions. 56 Physicians and nurses should, therefore, improve their knowledge of the field of phytotherapy, particularly because 90% of urological patients have reported currently taking or having previously taken some form of phytotherapeutic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientifically correct and personalized information enables patients to understand, evaluate and choose from a variety of safe and effective treatments in a conscious and truly autonomous manner. 52,55 This approach would also lay the necessary foundations for avoiding self-medication and autonomous therapeutic interruptions. 56 Physicians and nurses should, therefore, improve their knowledge of the field of phytotherapy, particularly because 90% of urological patients have reported currently taking or having previously taken some form of phytotherapeutic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although every patient has the right to therapeutic freedom, his or her healthcare must be centred on the use of safe and effective treatments. Scientifically correct and personalized information enables patients to understand, evaluate and choose from a variety of safe and effective treatments in a conscious and truly autonomous manner 52,55 . This approach would also lay the necessary foundations for avoiding self‐medication and autonomous therapeutic interruptions 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The Sit or Squat application was developed to help users find the nearest public restroom anywhere in the United States [14,15]. BladderPal and UroBladderDiary mobile applications help track urination and consumption [14][15][16]. Kegel Trainer PFM and Tät help to encourage and instruct users to conduct PFMT [9,10,17], and Tät provides additional resources aside from PFMT instructions, such as remedies to help address UI symptoms [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lobo et al showed that trained advanced practice providers with real-time urologist feedback for procedures such as cystoscopy has allowed for improved access to care without compromising on quality and further highlighting the untapped utility of telemedicine [26]. The development of mobile apps (mHealth), home-based diagnostics such as at-home semen analyses, wearable at home sensors with real time transmission of data to physicians has ramped up and will likely continue to be important noninvasive means of supplementing the core telehealth services we are now already familiar with [27–29]. Data from McKinsey et al has shown that investment in virtual care and digital health is nearly three times the level of venture capital digital health investment in 2017 promising a strong push to revolutionize this realm of healthcare [30].…”
Section: Advances In Telemedicinementioning
confidence: 99%